Compatibility of the electrical project with complementary disciplines in single-family homes: A bim-based approach (REVIT and NAVISWORKS) (Research, Society and Development, 2025)
Design coordination (compatibilization) is an essential early stage of any construction project, as it integrates the different disciplines involved with the primary aims of reducing costs, preventing waste, and minimizing rework. This study aims to analyze the set of project documents as a whole in order to identify errors that could cause interferences or even halt execution on site. The BIM (Building Information Modeling) methodology enables information management throughout the entire lifecycle of the asset—covering planning, design, construction, and operation. In this work, the electrical, architectural, structural, and water and sanitation disciplines were modeled in Revit®, using parametric families that provide greater accuracy in project deliverables. Coordination was performed in Navisworks®, which directly contributes to mitigating technical and operational risks by enabling early conflict detection (clash detection). This preventive approach enhances the identification of interferences that would otherwise be discovered only during construction, leading to delays and losses. It is concluded that applying BIM increases planning efficiency, enhances safety, optimizes the schedule, and ensures regulatory compliance.